2013
DOI: 10.1371/journal.pone.0069763
|View full text |Cite
|
Sign up to set email alerts
|

Resistance Development of Cystic Fibrosis Respiratory Pathogens When Exposed to Fosfomycin and Tobramycin Alone and in Combination under Aerobic and Anaerobic Conditions

Abstract: Although antibiotics from different classes are frequently prescribed in combination to prevent the development of resistance amongst Cystic Fibrosis (CF) respiratory pathogens, there is a lack of data as to the efficacy of this approach. We have previously shown that a 4∶1 (w/w) combination of fosfomycin and tobramycin (F∶T) has excellent activity against CF pathogens with increased activity under physiologically relevant anaerobic conditions. Therefore, the aim of this study was to determine whether F∶T coul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(19 citation statements)
references
References 31 publications
0
18
0
Order By: Relevance
“…were found (25). In the present study, the mean number of CFU obtained from bones of the no-treatment group (not weight based) was 2.7 ϫ 10 6 .…”
Section: ϫ8mentioning
confidence: 39%
“…were found (25). In the present study, the mean number of CFU obtained from bones of the no-treatment group (not weight based) was 2.7 ϫ 10 6 .…”
Section: ϫ8mentioning
confidence: 39%
“…This fact reinforces the need to administer tobramycin in combination with other compounds. Fosfomycin has demonstrated that it can enhance the active transport of tobramy- cin into the cell (10); furthermore, its activity does not decrease in anaerobiosis, and some studies have reported high activity under these conditions (16). It has also been reported that fosfomycintobramycin association is advantageous in anaerobiosis, as it downregulates the expression of nitrate reductase genes that are essential for the growth of P. aeruginosa (28).…”
Section: Discussionmentioning
confidence: 99%
“…Fosfomycin, tobramycin, and fosfomycin-tobramycin combination MPCs were calculated for three tobramycin-susceptible (Pa2, MIC ϭ 2 g/ml; Pa4, MIC ϭ 4 g/ml; Pa5, MIC ϭ 4 g/ml) and two tobramycin-resistant (Pa7, MIC ϭ 64 g/ml; Pa8, MIC ϭ 32 g/ml) isolates. MPCs were determined in aerobic and anaerobic conditions (16). Briefly, an initial inoculum of approximately 10 10 CFU/ml was placed onto Mueller-Hinton agar plates with twofold-increasing fosfomycin concentrations (16 to 2,048 g/ml) and tobramycin concentrations (0.5 to 512 g/ml) and with the fosfomycin-tobramycin combination.…”
Section: Methodsmentioning
confidence: 99%
“…These results are consistent with previous studies that have examined the activity of fosfomycin alone. 20 Under both aerobic and anaerobic conditions, inhibitory activity of fosfomycin lasted for 12 h but there was re-growth thereafter for both strains at antibiotic concentrations of × 4, × 8 and × 16 aerobic MIC (Figure 1). However, no emergence of fosfomycin resistance was detected when the antibiotic concentration below the MIC (at concentration of × 0.5 aerobic MIC) or above the MPC (at concentration of × 32 aerobic MIC).…”
Section: Discussionmentioning
confidence: 95%
“…20 Selection of resistant mutants were obtained by plating the high inocula (ca. 10 10 CFU) of parental strains on MH agar plates containing 25 μg ml -1 of glucose-6-phosphate and × 8 MIC of fosfomycin, and MICs were determined to confirm resistance.…”
Section: Biological Fitness Cost Of Mutantsmentioning
confidence: 99%